Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1053/rapm.2003.50134
|View full text |Cite
|
Sign up to set email alerts
|

Fascia iliaca compartment block for femoral bone fractures in prehospital care

Abstract: The fascia iliaca compartment block is a simple, inexpensive, and effective method of prehospital analgesia for femoral shaft fracture. A sensory block of the internal part of the thigh is an early predictive sign of optimal pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…It was mainly used to provide analgesia following surgical procedures in the hip, femur and knee, treatment of burns on the thigh and in prehospital treatment of fracture femur [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…It was mainly used to provide analgesia following surgical procedures in the hip, femur and knee, treatment of burns on the thigh and in prehospital treatment of fracture femur [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Few studies have demonstrated that a fascia iliac compartment (FIC) block provides effective analgesia for a fractured femur in terms of facilitating an adequate position for spinal anaesthesia or when administered either during pre-hospital management or in emergency departments. [6][7][8] Systemic analgesics, such as narcotics, are commonly used, but their side effects profile including respiratory depression, cognitive impairment, vomiting, urinary retention, and others limits their clinical utility during injuries of the head, chest, or abdomen. [9][10][11] Previous studies suggest that the use of local anesthesia using femoral nerve block (FNB) is a safe and effective method.…”
mentioning
confidence: 99%
“…It was mainly used to provide analgesia following surgical procedures in hip, femur, knee, treatment of burns on thigh and in prehospital treatment of fracture femur 12,13 . Single shot fascia iliaca block provides effective analgesia for positioning of the patient with proximal femur fracture during spinal anesthesia and also provides postoperative analgesia.…”
Section: Discussionmentioning
confidence: 99%